2023
DOI: 10.3389/fcell.2023.1123738
|View full text |Cite
|
Sign up to set email alerts
|

The auditory efferent system in mosquitoes

Abstract: Whilst acoustic communication forms an integral component of the mating behavior of many insect species, it is particularly crucial for disease-transmitting mosquitoes; swarming males rely on hearing the faint sounds of flying females for courtship initiation. That males can hear females within the din of a swarm is testament to their fabulous auditory systems. Mosquito hearing is highly frequency-selective, remarkably sensitive and, most strikingly, supported by an elaborate system of auditory efferent neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…However, mosquitoes possess serotonergic innervation of the primary auditory neurons of the Johnston organ (JO). This innervation is believed to be involved in the efferent control of hearing [ 75 , 76 ], and several types of 5-HT receptors (5-HT 1 , 5-HT 2 , and 5-HT 7 ) are expressed there [ 58 ]. Thoracically injected 5-HT caused an increase in the mechanical tuning frequency of the JO, reversed by the injection of methiothepin [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, mosquitoes possess serotonergic innervation of the primary auditory neurons of the Johnston organ (JO). This innervation is believed to be involved in the efferent control of hearing [ 75 , 76 ], and several types of 5-HT receptors (5-HT 1 , 5-HT 2 , and 5-HT 7 ) are expressed there [ 58 ]. Thoracically injected 5-HT caused an increase in the mechanical tuning frequency of the JO, reversed by the injection of methiothepin [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is highly expressed in many brain regions, including the primary olfactory center, the antennal lobe (AL) ( Okada et al, 2009 ), the optic lobe ( Raghu et al, 2013 ), the mushroom bodies (MBs) ( Yasuyama et al, 2002 )—a site involved in learning and memory ( Heisenberg et al, 1985 ; Davis, 1993 ), and the central complex ( Enell et al, 2007 ). Accordingly, GABA is involved in many different sensory behaviors, including the processing of odors ( Waldrop et al, 1987 ; Stopfer et al, 1997 ; Olsen and Wilson, 2008 ) and visual ( Brotz et al, 2001 ; Freifeld et al, 2013 ) and auditory stimuli ( Loh et al, 2023 ). The neuronal circuits and behaviors associated with learning and memory are also modulated by GABA, with GABAergic processes that broadly innervate the MBs ( Liu and Davis, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of GABA in mosquitoes, only a handful of studies have examined GABA expression in the mosquito brain ( Lahondère et al, 2020 ; Loh et al, 2023 ; Singh et al, 2023 ), and none have examined GABA-receptor expression. In particular, the GABA-B1-receptors are involved in many vital physiological processes and constitutes a promising pharmacological target in insecticide development where resistance problems targeting GABA A receptor subunit are now observed ( Zulfa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive GABAergic innervation of the mosquito auditory nerve (4,5), GABA’s role in audition has not been studied in detail. It has been shown that GABA is released from type I efferent terminals in the auditory nerve of Culex quinquefasciatus mosquitoes (4,5), where it modulates the mechanical frequency tuning and nerve responses.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive GABAergic innervation of the mosquito auditory nerve (4,5), GABA’s role in audition has not been studied in detail. It has been shown that GABA is released from type I efferent terminals in the auditory nerve of Culex quinquefasciatus mosquitoes (4,5), where it modulates the mechanical frequency tuning and nerve responses. We recently reported the transcriptome of the Anopheles gambiae ear (12), and found a number of GABA receptors expressed, including ionotropic (GABA A ) and metabotropic (GABA B ) receptors.…”
Section: Introductionmentioning
confidence: 99%